Summer Diet of the Bearded Seal (Erignathus barbatus) in the Canadian High Arctic - Finley, K.J.; Evans, C.R. (ARCTIC, 1983)
Stomach contents of 34 bearded seals taken in three High Arctic localities (Grise Fiord, Pond Inlet and Clyde) during the summers from 1978-1980 were examined. At least 12 species of fish were present but sculpins (Cottidae) and arctic cod (Boreogadus saida) comprised the bulk of the diet. Eelpouts (Lycodes spp.) and polar cod (Arctogadus glacialis) were also ingested in considerable amounts. In 15 of 19 stomachs containing > 1 kg food, fish contributed > 90% of the wet weight. The whelk Buccinem and the shrimp Sclerocrangon boreas accounted for most of the invertebrate component of the diet. Clams, cephalopods, anemones, sea cucumbers, polychaete worms and other invertebrates occurred in small amounts. The largest measured weight of stomach contents was 7.6 kg from a seal that had fed heavily on arctic cod. There were no significant differences amongst the three localities in the amount of food ingested; however, the proportions of arctic cod and sculpins varied considerably among localities. Bearded seals fed on the available size range of arctic cod but were limited to the smaller sculpins (<200 g), eelpouts (<200 g) and polar cod (<350 g).Key words: bearded seals, Canadian High Arctic, diet Mots clés: phoques barbus, nord de l'Arctique canadien, régime alimentaire